Characterizing the Pain Experience of Children With Acute Gastroenteritis Based on Identified Pathogens. Issue 2 (30th November 2022) - Ma, Keon; Ali, Samina; Xie, Jianling; Maki, Claudia; Lee, Bonita; Chui, Linda; Pang, Xiao-Li; Zhuo, Ran; Parsons, Brendon; Vanderkooi, Otto; Poonai, Naveen; MacDonald, Shannon E.; et al.
Abstract : Objectives: Pain is common with acute gastroenteritis (AGE) yet little is known about the severity associated with specific enteropathogens. We sought to explore the correlation of pain severity with specific enteropathogens in children with AGE. Methods: Participants were prospectively recruited by the Alberta Provincial Pediatric EnTeric Infection TEam at 2 pediatric emergency departments (EDs) (December 2014–August 2018). Pain was measured (by child and/or caregiver) using the 11-point Verbal Numerical Rating Scale. Results: We recruited 2686 participants; 46.8% (n = 1256) females, with median age 20.1 months (interquartile range 10.3, 45.3). The mean highest pain scores were 5.5 [standard deviation (SD) 3.0] and 4.2 (SD 2.9) in the 24 hours preceding the ED visit, and in the ED, respectively. Prior to ED visit, the mean highest pain scores with bacterial detection were 6.6 (SD 2.5), compared to 5.5 (SD 2.9) for single virus and 5.5 (SD 3.1) for negative stool tests. In the ED, the mean highest pain scores with bacterial detection were 5.5 (SD 2.7), compared to 4.1 (SD 2.9) for single virus and 4.2 (SD 3.0) for negative stool tests. Using multivariable modeling, factors associated with greater pain severity prior to ED visit included older age, fever, illness duration, number of diarrheal or vomiting episodes in the preceding 24 hours, and respiratory symptoms, but not enteropathogen type. Conclusion: Children with AGE experience significant pain, particularly when the episode is associated with the presence of a bacterial enteric pathogen. However, older age and fever appear to influence children's pain experiences more than etiologic pathogens.